A Tale of Mystery Shopping: Mausummery Perspective!. Issue 1 (March 2020) - Arif, Farrah; Sarfraz, Sarah S.
Mausummery, founded in the year 1997, designed and manufactured lawn (lightweight cotton) clothing in Lahore, Pakistan. As the lawn industry became more competitive and the product became homogeneous, the company wanted to focus on service excellence to differentiate its brand and achieve higher sales and market share. The company had opened a number of its own stores in the hope of providing outstanding customer service. However, mystery shopping research had shown the company stores performing poorly relative to the competition, despite the sales training. The CEO and COO had to decide how to handle the situation moving forward.